Efficient tax policy ranks education higher than saving - Wolfram F. Richter (Center for Economic Studies and ifo Institute (CESifo), 2007)
Assuming a two-period model with endogenous choices of labour, education, and saving, it is shown to be second-best efficient not to distort the choice of education. In general this implies distorting the saving decision. Hence a strict order of policy priority is derived. Efficient tax policy ranks investment in human capital higher than investment in nonhuman capital. The result assumes an isoelastic earnings function and holds else for arbitrary utility functions. Isoelasticity of earnings is justified with reference to the empirically well-founded power law of learning.
Keywords: H21; I28; J24; 330; Optimale Besteuerung; Second Best; Bildungsverhalten; Sparen; Bildungsinvestition; Investition; Lernprozess; Theorie